Experimental study of antigenicity test of Sweet Bee Venom in Guinea Pigs - Byung Jun Cho (Journal of Pharmacopuncture, 2011)
Objectives: This study was performed to examine the antigenic potential of pure melittin (Sweet Bee Venom - SBV) extracted from the bee venom by utilizing protein isolation method of gel filtration. Methods: All experiments were conducted at Biotoxtech (Chungwon, Korea), authorized a non-clinical studies institution, under the regulations of Good Laboratory Practice (GLP). Antigenic potential of SBV was examined by active systemic anaphylaxis (ASA) and passive cutaneous anaphylaxis (PCA) in guinea pigs. SBV was subcutaneously administered at 0.07 and 0.28㎎/㎏and also as a suspension with adjuvant (Freund's complete adjuvant: FCA). Ovalbumin (OVA) as a suspension with adjuvant was used to induce positive control response (5㎎/㎖- FCA). Results: 1. In the ASA test, experimental groups showed some symptoms of anaphylaxis like piloerection, hyperpnea and staggering gait. 2. In the PCA test, low dosage group did not show any antibody responses, whereas high dosage group showed positive responses. 3. In the weight measurement and clinical observation, experimental groups didn't show any significant changes compared with control group. 4. In the autopsy of body, the abnormalities of lung were detected in the corpse. This means that the cause of death may induced anaphylactic shock. Conclusions: Above findings suggested that SBV had antigenic potential in guinea pig. Further studies on the subject should be conducted to yield more concrete evidences.